Acidosis, non-invasive ventilation and mortality in hospitalised COPD exacerbations. Issue 1 (12th November 2010) - Roberts, C M; Stone, R A; Buckingham, R J; Pursey, N A; Lowe, D
Abstract : Background: Reports of non-invasive ventilation (NIV) use in clinical practice reveal higher mortality rates than in corresponding randomised clinical trials. Aim: To explore factors related to chronic obstructive pulmonary disease (COPD) admissions and NIV use that may explain some of the previously reported high mortality rates. Methods: National UK audit of clinical care of consecutive COPD admissions from March to May 2008. Retrospective case note audit with prospective case ascertainment. Participating units completed a web-based audit proforma of process and outcomes of clinical care. Results: 232 hospital units collected data on 9716 patients, mean age 73, 50% male. 1678 (20%) of those with gases recorded on admission were acidotic and another 6% became acidotic later. 1077 patients received NIV, 55% had a pH<7.26 and 49% (305/618) had or were still receiving high flow oxygen. 30% (136/453) patients with persisting respiratory acidosis did not receive NIV while 11% (15/131) of acidotic admissions had a pure metabolic acidosis and did. Hospital mortality was 25% (270/1077) for patients receiving NIV but 39% (86/219) for those with late onset acidosis and was higher in all acidotic groups receiving NIV than those treated without. Only 4% of patients receiving NIV who died had invasive mechanical ventilation. Conclusions: COPD admissions treated with NIV in usual clinical practice were severely ill, many with mixed metabolic acidosis. Some eligible patients failed to receive NIV, others received it inappropriately. NIV appears to be often used as a ceiling of treatment including patient groups in whom efficacy of NIV is uncertain. The audit raises concerns that challenge the respiratory community to lead appropriate clinical improvements across the acute sector.